Effect of Pathyadi Churna with Masthu in Amajirna w.s.r to Dyspepsia- A Case Study (International Journal of Ayurveda and Pharma Research, 2022)
Amajirna is a common clinical condition that has symptoms such as - Yadhabhukta Avidagdha Udgara, Praseka, Utkleda, Gatra Gaurava, Akshikoota sotha. As per classics, the treatment of Amajirna includes Dipana and Pachana. Amajirna has resemblance with dyspepsia. Dyspepsia or indigestion is a common gastro-intestinal disorder with symptoms like nausea, bloating, early satiety, post prandial fullness, abdominal discomfort etc. There are various causes for the occurrence of dyspepsia including micro-organisms. The present case report is of a 41 years old male with onset of symptoms such as nausea, bloating, abdominal discomfort, early satiety, Yadhabhukta Avidagdha Udgara (burping with the same taste of food consumed), Praseka (excess salivation) and Utkleda (nausea) since one or two weeks in every month for the last 6 months. He was taking antacids while coming to the OPD, and got temporary relief. Gradually, even after taking his normal diet, the symptoms started to re-occur and effect of his medications lasted for only a few weeks. The patient was given Pathyadi Churna with Masthu as Anupana for 7 days. It was observed after the completion of treatment that all the symptoms disappeared after 7 days. Also, no reoccurrence for the next 4 months. This shows the Pathyadi Churna with Masthu has a significant effect in relieving the symptoms of dyspepsia/Amajirna.